A potential lignocellulosic biomass based on banana waste for critical rare earths recovery from aqueous solutions. (September 2020) - Lapo, Byron; Bou, Jordi J.; Hoyo, Javier; Carrillo, Manuel; Peña, Karina; Tzanov, Tzanko; Sastre, Ana María
Abstract: Rare earth elements (REE) present multiple applications in technological devices but also drawbacks (scarcity and water contaminant). The current study aims to valorise the banana wastes - banana rachis (BR), banana pseudo-stem (BPS) and banana peel (BP) as sustainable adsorbent materials for the recovery of REE (Nd 3+, Eu 3+, Y 3+, Dy 3+ and Tb 3+ ). The adsorbent materials were characterized using analytical techniques such as: Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, zeta potential and scanning electron microscopy with energy dispersive X-ray probe. The adsorption performance and mechanisms were studied by pH dependence, equilibrium isotherms, kinetics, thermodynamics, ion-exchange and desorption evaluation. The results show good adsorption capacities for the three materials, highlighting BR that presents ∼100 mg/g for most of the REE. The adsorption process (100 mg REE/L) reaches the 60% uptake in 8 min and the equilibrium within 50 min. On the other hand, the thermodynamic study indicates that the adsorption is spontaneous and exothermic (ΔH° < 40 kJ/mol). The adsorption mechanism is based on the presence of carboxylic groups that induce electrostatic interactions and facilitate the surface nucleation of REE microcrystals coupled to an ion exchange process as well as the presence of other oxygen containing groups that establish weak intermolecular forces. The recovery of REE from the adsorbent (∼97%) is achieved using EDTA as desorbing solution. This research indicates that banana waste and particularly BR is a new and promising renewable bioresource to recover REE with high adsorption capacity and moderated processing cost. Graphical abstract: Image 1 Highlights: Banana waste can be applied in the recovery of critical rare earths. Banana rachis is a novel biosorbent with REE sorption capacity up to 100 mg/g. Electrostatic interactions are the main contribution for the sorption uptake.